2018
DOI: 10.18410/jebmh/2018/694
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic Resonance Imaging in Evaluation of Painful Hip Joint

Abstract: BACKGROUND Magnetic resonance imaging is an imaging modality that provides excellent soft tissue resolution, and with its multiplanar capability provides an excellent anatomical and biomechanical details and information. Hip joint with its weight bearing capability is an important synovial joint in human body. Painful hip is one of the important and common clinical presentations with wide variety of causes. The present study is undertaken to describe the various aetiologies and MRI features in patients with pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…The study done by El-Zawawi et al, [13] revealed the MRI findings in septic arthritis of hip were synovial thickening, joint effusion, soft-tissue edema, and bone marrow edema. Narra et al, [14] found the common MRI findings in patients with septic arthritis of hip as joint space narrowing, joint effusion, and periarticular soft-tissue edema.…”
Section: Septic Arthritismentioning
confidence: 99%
“…The study done by El-Zawawi et al, [13] revealed the MRI findings in septic arthritis of hip were synovial thickening, joint effusion, soft-tissue edema, and bone marrow edema. Narra et al, [14] found the common MRI findings in patients with septic arthritis of hip as joint space narrowing, joint effusion, and periarticular soft-tissue edema.…”
Section: Septic Arthritismentioning
confidence: 99%